2019
DOI: 10.1016/j.heliyon.2019.e02064
|View full text |Cite
|
Sign up to set email alerts
|

Detection of dental plaque with disclosing agents in the context of preventive oral hygiene training programs

Abstract: No studies have evaluated the relationship between the detection points for dental bacterial plaque (DBP or biofilm) and gender, age, socioeconomic status, body mass index (BMI), and oral health, hence the need to investigate and clarify their possible association. This study aimed to map out the occurrence of DBP, investigate and evaluate the factors affecting its localization, and design preventive interventions. The research was conducted on 588 public school children aged 4-18 years in a provincial area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 36 publications
0
19
0
11
Order By: Relevance
“…Dental disclosants stain plaque on enamel surfaces to help identify the degree and location of plaques, making it useful not only for professional dental treatment but also for personal oral care. Oral management education using dental disclosants is effective in promoting proper tooth brushing and oral hygiene due to its vibrant visual effect 12) , and helps prevent dental caries and periodontal diseases 12,13) . If liquid dental disclosants are washed after application, unnecessary staining can be controlled, but the quick dissolving tablet causes excessive staining in oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Dental disclosants stain plaque on enamel surfaces to help identify the degree and location of plaques, making it useful not only for professional dental treatment but also for personal oral care. Oral management education using dental disclosants is effective in promoting proper tooth brushing and oral hygiene due to its vibrant visual effect 12) , and helps prevent dental caries and periodontal diseases 12,13) . If liquid dental disclosants are washed after application, unnecessary staining can be controlled, but the quick dissolving tablet causes excessive staining in oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that oral health education using dental disclosing solution is effective in preventing dental caries and periodontitis (Fasoulas et al, 2019; Lee, Jung, & Pang, 2016). The primary cause of dental caries and periodontitis is the attachment of dental plaque to dental fissures and gingival sulcus.…”
Section: Discussionmentioning
confidence: 99%
“…Adding a disclosing agent into the toothpaste, makes it more convenient for chairside education and is easily obtainable for the patient to bring home and can cultivate an effective brushing habit [29]. Our questionnaire responses showed that 70% of participants who used disclosing tooth paste, felt more motivated to brush their teeth.…”
Section: Discussionmentioning
confidence: 80%